A proposed simplified API 579 assessment procedure for shakedown limit load determination with application to locally thinned wall pipe-branch connections - Hafiz, Youssef (AUC Knowledge Fountain, 2013)
In the current research, a new assessment procedure is proposed to determine the shakedown limit load of locally thinned wall pressurized components via modifying the current API 579 level-three assessment. The new assessment procedure applies a well-established and verified simplified technique, previously developed by Abdalla et al. [1], discarding iterative full elastic-plastic cyclic loading finite element (FE) analyses. For the purpose of validation, the newly proposed assessment procedure is applied to generate the shakedown boundary of a locally thinned wall pipe-branch connection subjected to a spectrum of steady internal pressures and cyclic bending moments. The outcomes of the proposed assessment procedure are successfully verified against existing API 579 assessment procedures, numerical analyses, and experimental outcomes taken from the literature. Interaction (Bree) diagrams illustrating elastic, shakedown, and limit load domains are constructed for the locally thinned wall pipe-branch connection problem. Additionally, a parametric study is performed through changing the both the depth and location of the local wall thinning within the pipe-branch connection. The outcomes of the parametric study show good agreement in the shakedown limit boundary results with the API 579 elastic-plastic stress analysis procedure.